« Je m’y promenais donc avec Dickens » L’influence des représentations littéraires sur la mémoire collective dans la théorie de Halbwachs - Florence Tilch (Conserveries Mémorielles)
Fictions, especially literary works, are very valuable sources when we try to understand how a community represents its past. However, we should be aware of the particular nature of those texts, and conceptualize their use before proceeding to any investigation of collective memory processes.Maurice Halbwachs was the first to reflect systematically on the conditions and consequences of the phenomenon of collective memory. This paper offers a reading of two works of the French sociologist in order to determine in which ways they still constitute a fertile foundation for a theory on the role of literary representations within a collective memory.